A comparison between two different doses of sublingual misoprostol in the management of first trimester incomplete miscarriage - Shakir, Ishraq M.; Mustafa, Mina J. (Zanco Journal of Medical Sciences (ZJMS), 2016)
Background and objective: Various methods have been described for management of first trimester incomplete miscarriage. The active methods include surgical methods that are highly effective but are associated with anesthetics and surgical risks. Medical methods by Misoprostol had been shown to be effective, acceptable and widely used treatment for incomplete miscarriage. The aim of this study was to compare the efficacy, patients’ acceptability and the side effects of sublingual administration of single dose of 400mcg with single dose of 600mcg of misoprostol in the treatment of first trimester incomplete miscarriage. Methods: This study was conducted from April 1st, 2011 to February 1st, 2012 in the Maternity Teaching Hospital in Erbil city, Kurdistan region, Iraq. The study included 120 patients with incomplete miscarriage at a gestational age ≤12 weeks. They randomly received either single dose of 400mcg or 600mcg of misoprostol sublingually. Patients returned for follow-up and re-evaluation of abortion status after 7 days. Patients with a continuous incomplete miscarriage underwent surgical evacuation. Results: The success rate in the first and second group was 90% and 91.7%, respectively, while patients’ acceptability in the first and second group was 96.7% and 95%, respectively with no difference between both groups. Gastrointestinal side effects like nausea and diarrhea were more in the second group. Conclusion: Single dose of 400 mcg of sublingual misoprostol is preferred on 600mcg of sublingual misoprostol regarding the development of side effects.